Low-Level Prenatal and Postnatal Blood Lead Exposure and Adrenocortical Responses to Acute Stress in Children - Gump, Brooks B. (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: A few recent studies have demonstrated heightened hypothalamic–pituitary–adrenal (HPA) axis reactivity to acute stress in animals exposed to heavy metal contaminants, particularly lead. However, Pb-induced dysregulation of the HPA axis has not yet been studied in humans. OBJECTIVE: In this study, we examined children’s cortisol response to acute stress (the glucocorticoid product of HPA activation) in relation to low-level prenatal and postnatal Pb exposure. METHODS: Children’s prenatal blood Pb levels were determined from cord blood specimens, and postnatal lead levels were abstracted from pediatrician and state records. Children’s adrenocortical responses to an acute stressor were measured using assays of salivary cortisol before and after administration of a standard cold pressor task. RESULTS: Pb exposure was not associated with initial salivary cortisol levels. After an acute stressor, however, increasing prenatal and postnatal blood Pb levels were independently associated with significantly heightened salivary cortisol responses. CONCLUSIONS: Our results suggest that relatively low prenatal and postnatal blood lead levels—notably those below the 10 μg/dL blood lead level identified by the Centers for Disease Control and Prevention for public health purposes—can alter children’s adrenocortical responses to acute stress. The behavioral and health consequences of this Pb-induced HPA dysregulation in children have yet to be determined.